Partial molecular characterization of the mitochondrial genome of Baylisascaris columnaris and prevalence of infection in a wild population of Striped skunks. Issue 2 (August 2017) - Choi, Youna; Mason, Sara; Ahlborn, Michael; Zscheile, Brook; Wilson, Eric
Abstract: Members of the genus Baylisascaris utilize omnivores or carnivores as their definitive hosts. The best known member of this genus is Baylisascaris procyonis, which is an intestinal parasite of raccoons. The closest relative of B. procyonis is B. columnaris, which utilizes the common skunk as its definitive host. Although B. procyonis has been extensively studied, relatively little is known of B. columnaris . For example, the mitochondrial genome of B. procyonis has been sequenced in its entirety. Conversely, the mitochondrial genome of B. columnaris remains largely unexplored. Likewise, the prevalence of this parasite in its wild host has not been documented. In this study, we collected parasites from a wild population of skunks in the state of Utah, United States. The cytochrome c oxidase subunit 1 and 2 genes, NADH dehydrogenase 2 and several tRNA genes were sequenced from the mitochondrial genome of these parasites. We also determined the prevalence of B. columnaris in a wild population of skunks. In this work we identify several novel polymorphic genetic loci between B. procyonis and B. columnaris . These findings provide additional molecular targets for the differentiation of Baylisascaris species through clarification of genetic differences between B. columnaris and B. procyonis . Graphical abstract: Highlights: Prevalence of B. columnaris infection in wild striped skunks ∼60%. Several mtDNA genes from B. columnaris sequenced. Mitochondrial gene sequences show several species specific SNPs in B. columnaris .